The mechanical and physical properties of concrete containing polystyrene beads as aggregate and palm oil fuel ash as cement replacement material - Adnan, Suraya Hani; Abadalla, Musab Alfatih Salim; Jamellodin, Zalipah (American Institute of Physics, 2017)
One of the disadvantages of normal concrete is the high self-weight of the concrete. Density of the normal concrete is in the range of 2200 kg/m3 to 2600 kg/ m3 .This heavy self-weight make it as an uneconomical structural material. Advantages of expended polystyrene beads in lightweight concrete is its low in density which can reduce the dead load (self-weight) Improper disposal of the large quantity of palm oil fuel ash which has been produced may contribute to environmental problem in future. In this study, an alternative of using palm oil fuel ash as a cement replacement material is to improve the properties of lightweight concrete. The tests conducted in this study were slump test, compression strength, splitting tensile and water absorption test. These samples were cured under water curing condition for 7, 28 and 56 days before testing. Eight types of mixtures were cast based on percentage (25%, 50%) of polystyrene beads replacement for control samples and (25%, 50%) of polystyrene beads by different ratio 10%, 15%, and 20% replacement of palm oil fuel ash, respectively. Samples with 25% polystyrene beads and 10% palm oil fuel ash obtained the highest compressive strength which is 16.8 MPa, and the splitting tensile strength is 1.57 MPa. The water absorption for samples 25%, 50% polystyrene and 20% palm oil fuel ash is 3.89% and 4.67%, respectively which is lower compared to control samples.